Study of variations in the pelvicalyceal system of kidney and its clinical importance - Wadekar, PR; Gangane, SD (Journal of College of Medical Sciences-Nepal, 2013)
Objective The present study has been undertaken to study the variations in renal pelvicalyceal system, to compare them with previous studies and to find their clinical implications. Materials and Methods A total of 100 kidneys (from 50 cadavers) were included in this study. The following parameters were measured 1)Lower Infundibular length, 2)Infundibular Width – Lower Infundibular Width (LIW), Middle Infundibular Width (MIW), Upper Infundibular Width (UIW), 3)Number of minor calyces and 4)Number of major calyces. Results The obtained data showed that there were numerous variations not only in the numbers of calyces of kidneys but also in the infundibular length and width. Conclusion Developments in endourology, percutaneous nephrolithotomy and techniques for retrograde percutaneous nephrostomy have rekindled interest in the anatomy of the renal collecting system. To perform these procedures safely and efficiently it is essential to have a clear understanding of pelvicalyceal anatomy and its variations. Thus the in-depth knowledge of pelvicalyceal anatomy will be of immense value to the clinicians of related specialties. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 17-21 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8681